Pengaruh Kualitas Pelayanan dan Penggunaan Teknologi Informasi Terhadap Kepatuhan Wajib Pajak - Meidhani Martha; Sumiati , Sumiati (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to analyze the influencequality of service and use of information technology on taxpayer compliance with the Padang One Roof Manunggal Administration System. This research uses quantitative methods. The population is the total number of taxpayers complying with the Padang One-Stop Single Administration System tax service office, the sampling technique is random sampling with anyone observing at the survey location. Data analysis uses multiple linear regression analysis using the SPSS application. The research results show that service quality has a positive effect on taxpayer compliance in the Padang One-Stop Single Administration System and the use of information technology has a positive effect on taxpayer compliance in the Padang One-Stop Single Administration System.